UMKM Cimol Bojot sebagai Peluang Usaha Kuliner Khas Tantangan dan Prospek - Indah Suci Andryani; Guntur Haludin; Zahra Dhitalia Hidayat; Yesi Elhanza Aprilian; Jacinda Fawnia Apriliyani; Dadys Ananda Hendri (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This research applies linear programming methods to optimize resource allocation in the UMKM Cimol Bojot AA. The main problems faced include raw material limitations and difficulties in determining the optimal production combination of four product variants with different profitability. Through a quantitative approach, mathematical modeling was carried out on decision variables, objective functions to maximize profits, and resource constraints. Data was obtained through interviews and direct observation of the production process. Analysis results using manual calculations and QM for Windows show that the optimal production combination is 0 portions of Original Cimol, 9 portions of Spicy Cimol, 13 portions of Cheese Cimol, and 13 portions of Chicken-Filled Cimol, with a maximum profit of IDR 128,958 per day. The research findings prove the effectiveness of linear programming in solving operational problems of MSMEs and providing a more measurable basis for decision-making. Further research can apply integer linear programming methods and sensitivity analysis to accommodate fluctuations in raw material prices.